Lightweight high-strength conductive rubber material and preparation method thereof

By using a combination of porous structure and dense rubber layer in rubber materials, combined with three -dimensional polyitable conductive skeleton materials and silver graphene fiber, the problem of difficulty in the existing rubber material is difficult to have light and high -mechanical strength. The comprehensive improvement of quality, high -strength and conductive effects has broaden its application field.

CN119331302APending Publication Date: 2025-01-21SUZHOU DINGLI IND RUBBER ROLLER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411429905.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing rubber materials are difficult to have light weight and high mechanical strength, and lack good conductive effects, which limits their application areas.

Method used

Through the combination of internal porous structures and external rubber layers in rubber materials, combined with three -dimensional polyiteric conductive skeleton materials and silver graphene fiber to form a rich conductive network and powerful mechanical properties.

Benefits of technology

It achieves lightweight, high strength and good conductive effects, broadening the application fields of rubber materials, especially in the fields of aerospace, new energy vehicles and high-speed railways.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331302A_ABST
    Figure CN119331302A_ABST
Patent Text Reader

Abstract

The invention provides a light high-strength conductive rubber material and a preparation method thereof. The preparation method comprises the following steps: adding a three-dimensional porous conductive framework material into methyl vinyl silicone rubber, mixing, adding a composite foaming agent, hydroxyl silicone oil, BPO and the like, mixing, and standing; remilling: adding chloroplatinic acid and uniformly milling; vulcanizing to obtain porous conductive rubber; immersing the porous conductive rubber into concentrated hydrochloric acid, cleaning and drying; coating gamma-aminopropyltriethoxysilane on the surface, reacting at 70 DEG C under the protection of N2, and drying; hydroxyl-terminated polydimethylsiloxane, a polycarbonate prepolymer, silver-loaded graphene fibers, ethyl orthosilicate and dibutyltin dilaurate are mixed and stirred uniformly, the surface of the porous conductive rubber is coated and cured, a compact conductive rubber layer is formed, and the conductive rubber is obtained. By adopting the internal porous structure, the purpose of light weight is achieved, meanwhile, the surface of the rubber is coated with the compact rubber layer, so that the effect of high strength is achieved, and the structure has the advantages of light weight and high strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The invention relates to the field of functional rubber, and in particular to a lightweight and high-strength conductive rubber material and a preparation method thereof. Background Art As a polymer between inorganic and organic materials, silicone rubber has both the flexibility of organic materials and the thermal stability of inorganic materials, so it has a special and wide range of applications. In recent years, with the continuous development of my country's and the world's economy, the rise of emerging industries such as aerospace, new energy vehicles, and high-speed railways, the demand for silicone rubber foam has increased, and the requirements for various performance indicators of silicone rubber foam have continued to increase. The silicone rubber foam materials produced can no longer meet market demand. Functionalized and high-performance silicone rubber foam materials are one of the most popular materials in the field of foam materials. Generally speaking, porous silicone rubber has the advantage of light weight, but it is precisely because of the advantage of light weight that it cannot have good mechanical properties. It often has poor mechanical properties and cannot meet the specified requirements, and its application is also limited. Therefore, it is of great significance to study silicone rubber that is both light and has high-strength mechanical properties. At the same time, how to give it a good conductive effect can further broaden its application field. Summary of the invention

[0003] Technical problem to be solved: The present invention aims to solve the technical problem that the current rubber cannot have both light weight and high mechanical strength. The purpose of light weight is achieved by adopting an internal porous structure. At the same time, a dense rubber layer is coated on the rubber surface to obtain a high strength effect. This structure can obtain the advantages of light weight and high strength.

[0004] Technical solution: A light and high-strength conductive rubber material, wherein the interior of the light and high-strength conductive rubber material is porous conductive rubber and the exterior is covered with a dense conductive rubber layer. The method for preparing the above-mentioned lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 15-30 parts of three-dimensional porous conductive skeleton material to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 3-6 parts of composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of vulcanization aid, and 0.4 parts of hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 2-3 hours, and leave for 24 hours; S2: Re-refining for 10-20 minutes, adding 0.12-0.15 parts of chloroplatinic acid and refining evenly; S3: Place the rubber in the mold, repeatedly add and release pressure to remove air from the rubber, perform vulcanization, and demould to obtain the porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 10-30 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 3-6 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.2-0.6 parts of silver-loaded graphene fiber, 2-3 parts of ethyl orthosilicate and 0.01-0.02 parts of dibutyltin dilaurate, stir evenly, apply it on the surface of the porous conductive rubber, and cure it at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Furthermore, the particle size of the three-dimensional porous conductive skeleton material is 20-100 μm. Furthermore, the preparation method of the three-dimensional porous conductive skeleton material is: S11: Take konjac gum powder, dissolve it in water, stir rapidly, heat it in a 90° C. water bath, stir continuously until it is completely hydrated, and balance at room temperature for 12 h to obtain a 3% konjac gum solution; S12: Take curdlan powder, disperse it in water, stir rapidly, heat it in a water bath at 60° C., and stir continuously to obtain a 5% curdlan solution; S13: 100 parts of konjac gum solution, 5-10 parts of curdlan gum solution, 0.2-0.6 parts of graphene fiber and 10-30 parts of water are mixed, placed in a 90° C. water bath and heated, and stirred until completely mixed; S14: Add 8-10 parts of 40% sodium carbonate solution, stir rapidly for 1 minute, stir evenly, place in a 90°C water bath and heat for 2 hours, take out, and equilibrate at room temperature for 12 hours; S15: freeze drying and crushing to obtain a three-dimensional porous conductive skeleton material. Furthermore, the graphene fiber has a diameter of 0.3-1.5 μm and a length of 3-8 μm. Furthermore, the composite foaming agent is a foaming agent AC and an auxiliary foaming agent urea derivative, and the mass ratio is 2:(0.8-1.1). Furthermore, the vulcanization conditions are: the first stage vulcanization temperature is 160° C., the vulcanization time is 10 min, and the second stage vulcanization temperature is 200° C., and the vulcanization time is 20 min. Furthermore, the preparation method of the silver-loaded graphene fiber is as follows: take 100 mg of graphene fiber and disperse it in 50 mL of water to obtain a graphene fiber dispersion; dissolve 100 mg of AgNO3 in 10 mL of water, and drop 3 wt.% of ammonia water into the AgNO3 aqueous solution until the precipitate just disappears to obtain a silver ammonia solution; mix the silver ammonia solution with 50 mL of the graphene fiber dispersion at 50°C, and add 1 g of PEG-400 at the same time, stir well for 1 hour, keep warm at 120°C in a hydrothermal reactor for 2 hours, wash the product with water and ethanol after cooling, and place it at 60°C to vacuum dry. Furthermore, the graphene fiber has a diameter of 0.01-0.5 μm and a length of 1-10 μm. Beneficial effects: 1. The present invention achieves the purpose of light weight by adopting an internal porous structure. At the same time, a dense rubber layer is coated on the rubber surface to obtain a high strength effect. This structure can obtain the advantages of light weight and high strength. 2. the present invention has added three-dimensional porous conductive skeleton material inside porous conductive rubber, on the one hand, skeleton support can be provided for rubber porous structure, on the other hand, abundant conductive network can be formed. By copolymerizing konjac glucomannan and curdlan, and adopting freeze drying, acquisition has specific guiding structure, set up a powerful network, and due to containing abundant functional groups on konjac glucomannan and curdlan, there is very strong polar interaction with the functional groups on graphene fiber, the network formed by konjac glucomannan and curdlan, is conducive to the uniform dispersion and fixing of graphene fiber, graphene fiber is evenly dispersed in network, ensures enough electronic transmission, simultaneously due to the fiber structure of graphene fiber, can increase the interweaving of network structure, strengthens conductive effect. 3. The present invention treats the porous conductive rubber with concentrated hydrochloric acid for a short time, thereby increasing the surface hydroxyl content, increasing the number of surface active reaction sites, and greatly enhancing the grafting reaction effect of γ-aminopropyltriethoxysilane and the porous conductive rubber. When the room temperature condensation-cured terminal hydroxyl polydimethylsiloxane is coated on its surface, the silane coupling agent chemically bonded to the surface of the porous conductive rubber can condense with the terminal hydroxyl polydimethylsiloxane, thereby effectively improving the interface adhesion between the porous conductive rubber and the dense rubber layer. 4. The present invention uses polycarbonate prepolymer and terminal hydroxyl polydimethylsiloxane to form an interpenetrating polymer network, which can not only improve the crosslinking degree of the polymer network, thereby improving its density, but also improve the mechanical properties of the dense layer due to the increase and enhancement of the network structure, and increase the conductivity through a more complex network structure. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is a schematic structural diagram of a lightweight and high-strength conductive rubber material in an embodiment, in which: 1. porous conductive rubber; 2. dense conductive rubber layer. DETAILED DESCRIPTION Example 1 A method for preparing a three-dimensional porous conductive skeleton material is as follows: S11: Take konjac gum powder, dissolve it in water, stir rapidly, heat it in a 90° C. water bath, stir continuously until it is completely hydrated, and balance at room temperature for 12 h to obtain a 3% konjac gum solution; S12: Take curdlan powder, disperse it in water, stir rapidly, heat it in a water bath at 60° C., and stir continuously to obtain a 5% curdlan solution; S13: 100 parts of konjac gum solution, 5 parts of curdlan gum solution, 0.5 parts of graphene fiber with a diameter of 0.3-1.5 μm and a length of 3-8 μm and 30 parts of water were mixed, placed in a 90° C. water bath and heated, and stirred until completely mixed; S14: Add 9 parts of 40% sodium carbonate solution, stir rapidly for 1 min, stir evenly and heat in a 90°C water bath for 2 h, take out and equilibrate at room temperature for 12 h; S15: freeze drying and crushing to obtain a three-dimensional porous conductive skeleton material. Example 2 A method for preparing a three-dimensional porous conductive skeleton material is as follows: S11: Take konjac gum powder, dissolve it in water, stir rapidly, heat it in a 90° C. water bath, stir continuously until it is completely hydrated, and balance at room temperature for 12 h to obtain a 3% konjac gum solution; S12: Take curdlan powder, disperse it in water, stir rapidly, heat it in a water bath at 60° C., and stir continuously to obtain a 5% curdlan solution; S13: 100 parts of konjac gum solution, 8 parts of curdlan gum solution, 0.5 parts of graphene fiber with a diameter of 0.3-1.5 μm and a length of 3-8 μm and 30 parts of water were mixed, placed in a 90° C. water bath and heated, and stirred until completely mixed; S14: Add 9 parts of 40% sodium carbonate solution, stir rapidly for 1 min, stir evenly and heat in a 90°C water bath for 2 h, take out and equilibrate at room temperature for 12 h; S15: freeze drying and crushing to obtain a three-dimensional porous conductive skeleton material. Example 3 A method for preparing a three-dimensional porous conductive skeleton material is as follows: S11: Take konjac gum powder, dissolve it in water, stir rapidly, heat it in a 90° C. water bath, stir continuously until it is completely hydrated, and balance at room temperature for 12 h to obtain a 3% konjac gum solution; S12: Take curdlan powder, disperse it in water, stir rapidly, heat it in a water bath at 60° C., and stir continuously to obtain a 5% curdlan solution; S13: 100 parts of konjac gum solution, 10 parts of curdlan gum solution, 0.5 parts of graphene fiber with a diameter of 0.3-1.5 μm and a length of 3-8 μm and 30 parts of water were mixed, placed in a 90° C. water bath and heated, and stirred until completely mixed; S14: Add 9 parts of 40% sodium carbonate solution, stir rapidly for 1 min, stir evenly and heat in a 90°C water bath for 2 h, take out and equilibrate at room temperature for 12 h; S15: freeze drying and crushing to obtain a three-dimensional porous conductive skeleton material. Example 4 A method for preparing a three-dimensional porous conductive skeleton material is as follows: S11: Take konjac gum powder, dissolve it in water, stir rapidly, heat it in a 90° C. water bath, stir continuously until it is completely hydrated, and balance at room temperature for 12 h to obtain a 3% konjac gum solution; S12: Take curdlan powder, disperse it in water, stir rapidly, heat it in a water bath at 60° C., and stir continuously to obtain a 5% curdlan solution; S13: 100 parts of konjac gum solution, 8 parts of curdlan gum solution, 0.2 parts of graphene fibers with a diameter of 0.3-1.5 μm and a length of 3-8 μm and 30 parts of water were mixed, placed in a 90° C. water bath and heated, and stirred until completely mixed; S14: Add 9 parts of 40% sodium carbonate solution, stir rapidly for 1 min, stir evenly and heat in a 90°C water bath for 2 h, take out and equilibrate at room temperature for 12 h; S15: freeze drying and crushing to obtain a three-dimensional porous conductive skeleton material. Example 5 A method for preparing a three-dimensional porous conductive skeleton material is as follows: S11: Take konjac gum powder, dissolve it in water, stir rapidly, heat it in a 90° C. water bath, stir continuously until it is completely hydrated, and balance at room temperature for 12 h to obtain a 3% konjac gum solution; S12: Take curdlan powder, disperse it in water, stir rapidly, heat it in a water bath at 60° C., and stir continuously to obtain a 5% curdlan solution; S13: 100 parts of konjac gum solution, 8 parts of curdlan gum solution, 0.6 parts of graphene fibers with a diameter of 0.3-1.5 μm and a length of 3-8 μm and 30 parts of water were mixed, placed in a 90° C. water bath and heated, and stirred until completely mixed; S14: Add 9 parts of 40% sodium carbonate solution, stir rapidly for 1 min, stir evenly and heat in a 90°C water bath for 2 h, take out and equilibrate at room temperature for 12 h; S15: freeze drying and crushing to obtain a three-dimensional porous conductive skeleton material. Comparative Example 1 The difference between this comparative example and Example 2 is that no curdlan is added, as follows: A method for preparing a three-dimensional porous conductive skeleton material is as follows: S11: Take konjac gum powder, dissolve it in water, stir rapidly, heat it in a 90° C. water bath, stir continuously until it is completely hydrated, and balance at room temperature for 12 h to obtain a 3% konjac gum solution; S12: 108 parts of konjac gum solution, 0.5 parts of graphene fibers with a diameter of 0.3-1.5 μm and a length of 3-8 μm and 30 parts of water were mixed, placed in a 90° C. water bath and heated, and stirred until completely mixed; S13: Add 9 parts of 40% sodium carbonate solution, stir rapidly for 1 min, stir evenly, heat in a 90°C water bath for 2 h, take out, and equilibrate at room temperature for 12 h; S15: freeze drying and crushing to obtain a three-dimensional porous conductive skeleton material. Comparative Example 2 The difference between this comparative example and Example 2 is that graphene fiber is replaced by graphene powder, specifically as follows: A method for preparing a three-dimensional porous conductive skeleton material is as follows: S11: Take konjac gum powder, dissolve it in water, stir rapidly, heat it in a 90° C. water bath, stir continuously until it is completely hydrated, and balance at room temperature for 12 h to obtain a 3% konjac gum solution; S12: Take curdlan powder, disperse it in water, stir rapidly, heat it in a water bath at 60° C., and stir continuously to obtain a 5% curdlan solution; S13: 100 parts of konjac gum solution, 8 parts of curdlan gum solution, 0.5 parts of graphene powder with a particle size of 10-50 μm and 30 parts of water were mixed, placed in a 90° C. water bath and heated, and stirred until completely mixed; S14: Add 9 parts of 40% sodium carbonate solution, stir rapidly for 1 min, stir evenly and heat in a 90°C water bath for 2 h, take out and equilibrate at room temperature for 12 h; S15: freeze drying and crushing to obtain a three-dimensional porous conductive skeleton material. Determination of porosity, compressive strength and conductivity of three-dimensional porous conductive skeleton materials: Determination of compressive strength: The compressive strength of the sample was measured using a texture analyzer with a P / 100 flat-bottom probe. The test parameters were: pre-test rate of 1 mm / s, test rate of 0.5 mm / s, and post-test rate of 2.0 mm / s. Conductivity determination: The three-dimensional porous conductive skeleton material sample was placed on the test bench of a four-probe conductivity tester. The test current was 10 μA. The sample was a disc with a thickness of 2 mm and a diameter of 22 mm. The results are shown in Table 1 below: Table 1 Porosity (%) Compressive strength(MPa) Electrical conductivity (S / m) Example 1 84.3 1.16 63.2 Example 2 84.1 1.25 63.8 Example 3 84.0 1.26 64.1 Example 4 84.6 1.03 49.6 Example 5 83.9 1.21 68.5 Comparative Example 1 86.0 0.95 58.9 Comparative Example 2 83.7 1.17 61.2 Taking into account various properties of the three-dimensional porous conductive skeleton material, including light weight, compressive strength and conductivity, the three-dimensional porous conductive skeleton material prepared in Example 2 was selected for subsequent experiments. Example 6 The preparation method of silver-loaded graphene fiber is as follows: take 100 mg of graphene fiber with a diameter of 0.01-0.5 μm and a length of 1-10 μm and disperse it in 50 mL of water to obtain a graphene fiber dispersion; dissolve 100 mg of AgNO3 in 10 mL of water, and drop 3 wt.% of ammonia water into the AgNO3 aqueous solution until the precipitate just disappears to obtain a silver ammonia solution; mix the silver ammonia solution with 50 mL of the graphene fiber dispersion at 50°C, add 1 g of PEG-400, stir well for 1 hour, keep warm at 120°C in a hydrothermal reactor for 2 hours, wash the product with water and ethanol after cooling, and place it at 60°C to vacuum dry. Example 7 A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 15 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:1.0; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 5 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.5 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Example 8 A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 25 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:1.0; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 5 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.5 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Example 9 A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: 30 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm are added to 60 parts of methyl vinyl silicone rubber, and mixed on a double-roll mill. At the same time, 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent are added in two portions, mixed for 3 hours, and allowed to stand for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:1.0; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 5 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.5 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Example 10 A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 25 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:0.8; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 5 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.5 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Embodiment 11 A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 25 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:1.1; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 5 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.5 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Example 12 A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 25 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:1.0; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 3 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.5 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Embodiment 13 A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 25 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:1.0; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 6 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.5 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Embodiment 14 A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 25 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:1.0; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 5 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.2 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Embodiment 15 A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 25 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:1.0; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 5 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.6 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Comparative Example 3 The difference between this embodiment and embodiment 8 is that no composite foaming agent is used, and all foaming agents AC are used, specifically: A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 25 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a two-roll mill, and add 5 parts of foaming agent AC, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of vulcanizing aid, and 0.4 parts of hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 5 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.5 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Comparative Example 4 The difference between this embodiment and embodiment 8 is that silver-loaded graphene fibers are not used, but graphene fibers are directly used. Specifically: a method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 25 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:1.0; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 5 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.5 parts of graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyl tin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. Comparative Example 5 The difference between this embodiment and embodiment 8 is that no polycarbonate prepolymer is added. Specifically: A method for preparing a lightweight and high-strength conductive rubber material comprises the following steps: S1: Add 25 parts of a three-dimensional porous conductive skeleton material with a particle size of 20-100 μm to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 5 parts of a composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of a vulcanizing aid, and 0.4 parts of a hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 3 hours, and leave for 24 hours; the composite foaming agent is a foaming agent AC and a co-foaming agent N-type urea-stearic acid complex, with a mass ratio of 2:1.0; S2: Re-refining for 20 min, adding 0.15 parts of chloroplatinic acid and refining evenly; S3: In the mold, repeatedly add and release pressure to remove the air in the rubber material and vulcanize it. The vulcanization conditions are: the first stage vulcanization temperature is 160°C, the vulcanization time is 10 minutes, the second stage vulcanization temperature is 200°C, the vulcanization time is 20 minutes, and the demoulding is porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 20 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 6 parts of terminal hydroxyl polydimethylsiloxane, 0.5 parts of silver-loaded graphene fiber, 3 parts of ethyl orthosilicate and 0.02 parts of dibutyltin dilaurate, stir evenly, coat the porous conductive rubber surface, and cure at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material. All the materials of each embodiment are made into Figure 1 The cylindrical structure shown has a porous conductive rubber interior with a diameter of 3 cm and is covered with a dense conductive rubber layer with a thickness of 0.1 cm. Determine its overall density, and determine its mechanical strength and electrical conductivity according to national standards: Tensile strength test: electronic tensile testing machine is used to test according to the national standard GB / T528-2009, and the tensile rate is 10mm / min; Hardness test: Cut the sample into 5cm thickness and test it with Shore hardness tester according to ISO 2439-2009. Test it at 5 different parts of the sample and take the average value. Conductivity (σ) test: σ is the reciprocal of volume resistivity (ρ). The test voltage is 500V. The volume resistivity (R) can be directly measured. The ρ of the material can be calculated using the following formula: Where: S is the effective area of ​​the electrode, which is 21.24 cm 2 , t is the sample thickness, cm. Table 2

Claims

1. A lightweight and high-strength conductive rubber material, characterized in that: The light-weight and high-strength conductive rubber material has porous conductive rubber inside and is coated with a dense conductive rubber layer outside.

2. The method for preparing a lightweight and high-strength conductive rubber material according to claim 1, characterized in that: The following steps are involved: S1: Add 15-30 parts of three-dimensional porous conductive skeleton material to 60 parts of methyl vinyl silicone rubber, mix on a double-roll mill, and add 3-6 parts of composite foaming agent, 6 parts of hydroxy silicone oil, 1.6 parts of BPO, 0.8 parts of vulcanization aid, and 0.4 parts of hydrogen-containing polysiloxane crosslinking agent in two portions, mix for 2-3 hours, and leave for 24 hours; S2: Re-refining for 10-20 minutes, adding 0.12-0.15 parts of chloroplatinic acid and refining evenly; S3: Place the rubber in the mold, repeatedly add and release pressure to remove air from the rubber, perform vulcanization, and demould to obtain the porous conductive rubber; S4: immerse the porous conductive rubber in concentrated hydrochloric acid for 10-30 seconds, take it out, wash it with water and dry it; S5: coating the surface with γ-aminopropyltriethoxysilane, reacting at 70°C for 5 h under N2 protection, and drying; S6: Mix 3-6 parts of terminal hydroxyl polydimethylsiloxane, 1 part of polycarbonate prepolymer, 0.2-0.6 parts of silver-loaded graphene fiber, 2-3 parts of ethyl orthosilicate and 0.01-0.02 parts of dibutyltin dilaurate, stir evenly, apply it on the surface of the porous conductive rubber, and cure it at 37°C for 12 hours to form a dense conductive rubber layer, thereby obtaining a lightweight and high-strength conductive rubber material.

3. The method for preparing a lightweight and high-strength conductive rubber material according to claim 2, characterized in that: The particle size of the three-dimensional porous conductive skeleton material is 20-100 μm.

4. The method for preparing a lightweight and high-strength conductive rubber material according to claim 2, characterized in that: The preparation method of the three-dimensional porous conductive skeleton material is: S11: Take konjac gum powder, dissolve it in water, stir rapidly, heat it in a 90° C. water bath, stir continuously until it is completely hydrated, and balance at room temperature for 12 h to obtain a 3% konjac gum solution; S12: Take curdlan powder, disperse it in water, stir rapidly, heat it in a water bath at 60° C., and stir continuously to obtain a 5% curdlan solution; S13: 100 parts of konjac gum solution, 5-10 parts of curdlan gum solution, 0.2-0.6 parts of graphene fiber and 10-30 parts of water are mixed, placed in a 90° C. water bath and heated, and stirred until completely mixed; S14: Add 8-10 parts of 40% sodium carbonate solution, stir rapidly for 1 minute, stir evenly, place in a 90°C water bath and heat for 2 hours, take out, and equilibrate at room temperature for 12 hours; S15: freeze drying and crushing to obtain a three-dimensional porous conductive skeleton material.

5. The method for preparing a lightweight and high-strength conductive rubber material according to claim 4, characterized in that: The graphene fiber has a diameter of 0.3-1.5 μm and a length of 3-8 μm.

6. The method for preparing a lightweight and high-strength conductive rubber material according to claim 2, characterized in that: The composite foaming agent is a foaming agent AC and an auxiliary foaming agent urea derivative, and the mass ratio is 2:(0.8-1.1).

7. The method for preparing a lightweight and high-strength conductive rubber material according to claim 2, characterized in that: The vulcanization conditions are as follows: the first stage vulcanization temperature is 160° C., the vulcanization time is 10 min, and the second stage vulcanization temperature is 200° C., the vulcanization time is 20 min.

8. The lightweight and high-strength conductive rubber material according to claim 2, characterized in that: The preparation method of the silver-loaded graphene fiber is as follows: 100 mg of graphene fiber is dispersed in 50 mL of water to obtain a graphene fiber dispersion; 100 mg of AgNO3 is dissolved in 10 mL of water, and 3 wt.% of ammonia water is dripped into the AgNO3 aqueous solution until the precipitate just disappears, to obtain a silver ammonia solution; the silver ammonia solution is mixed and stirred with 50 mL of the graphene fiber dispersion at 50° C., and 1 g of PEG-400 is added at the same time, and stirred thoroughly for 1 hour, and kept warm at 120° C. for 2 hours in a hydrothermal reactor, and after cooling, the product is washed with water and ethanol, and placed at 60° C. for vacuum drying to obtain the product.

9. The method for preparing a lightweight and high-strength conductive rubber material according to claim 8, characterized in that: The graphene fiber has a diameter of 0.01-0.5 μm and a length of 1-10 μm.